2017
DOI: 10.1007/s00404-017-4374-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization when men, women, or both partners are positive for HIV: a case–control study

Abstract: Our data suggest that IVF outcomes were similar to controls when men were HIV-positive and remain acceptable when women were HIV-positive. IVF outcomes were severely reduced in our sero-concordant couples; however, many patients had severe HIV disease previously, and therefore, these results should be reassessed in patients treated early in their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…In the ''women HIV'' group, implantation rate, clinical pregnancy rate (by transfer and by oocyte retrieval), and live birth rate (by transfer) were significantly lower compared with those of controls. In 2017, Vankerkem et al (20) found similar results in a case-control study (higher cancellation rate, lower number of oocytes, and lower clinical transfer rate and oocyte retrieval rate in the ''women HIV'' group).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the ''women HIV'' group, implantation rate, clinical pregnancy rate (by transfer and by oocyte retrieval), and live birth rate (by transfer) were significantly lower compared with those of controls. In 2017, Vankerkem et al (20) found similar results in a case-control study (higher cancellation rate, lower number of oocytes, and lower clinical transfer rate and oocyte retrieval rate in the ''women HIV'' group).…”
Section: Discussionmentioning
confidence: 73%
“…In their 2011 study, Santulli et al ( 18) had higher cancellation rates and significantly lower clinical pregnancy rates by oocyte retrieval in HIV-infected female and male couples vs. controls. In 2017, Vankerkem et al (20) did not show any significant difference in the outcome of HIV couples compared with HIV-negative controls. However, a negative trend was found for HIV couples with a live birth rate of 3% vs. 12% in the control group (P ¼ .3) and an evolutionary clinical pregnancy rate per transfer of 5% vs. 15% in the control group (P ¼ .28).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies are reported in literature, investigating the clinical outcomes of HIV‐ or HCV‐seropositive men, but very few with a case–control study design. Some authors believed that male HIV infection has no effect on fertilization, implantation, pregnancy and live birth rates (Melo et al ., ; Yang et al ., ; Vankerkem et al ., ). Equally, two out of the three matched control studies in literature did not find differences in clinical pregnancy rates (Santulli et al ., ; Prisant et al ., ), whereas the third one detected higher rates of FR and PR/C for cases involving HIV‐positive men (Kashima et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[24][25][26]. Показательными являются доказанные сведения о повреждающем действии на клетку АРТ, применяемой при лечении ВИЧ-инфицированных пациенток [11,12]. Известно, что операции на яичниках значительно снижают овариальный резерв [13,14].…”
Section: вспомогательные репродуктивные технологии Assisted Reproductunclassified